EBSD study on microstructure and texture of friction stir welded AA5052-O and AA6061-T6 dissimilar joint. (15th December 2015) - Wang, Bin; Lei, Bo-bo; Zhu, Jia-xiang; Feng, Quan; Wang, Liang; Wu, Deng
Abstract: Friction stir welded AA5052-O and AA6061-T6 dissimilar joint has a more obvious impact on microstructure and texture evolution compared to single material welding due to differences in physical and chemical parameters between two aluminum alloys. Microstructure, texture evolution and grain structure of AA5052-O and AA6061-T6 dissimilar joint were investigated by means of OM, EBSD and TEM measurements. Experimental results showed that FS weld was generalized in four regions–nugget zone (NZ), thermomechanically affected zone (TMAZ), heat affected zone (HAZ) and base metals (BM), using standard nomenclatures. NZ exhibited the complex structure of the two materials with flowing shape and mainly composed of the advancing side material Subgrain boundaries in weld nugget zone gradually transformed into high angle grain boundaries by absorbing dislocation and accumulating misorientations. Grain refinement of weld nugget zone was achieved by dynamic recrystallization. In the friction stir welding process, the presence of the shear deformation in weld made {001} < 100 > C cube texture, {123} < 634 > S texture in BM gradually transformed into {111} < 1(−)12(−) > A1 ∗ shear texture. HABs distribution were most significant in nugget followed by RS and then by AS. In TMAZ and NZ, numerous precipitates and lots of dislocations were observed. Graphical abstract: Highlights: There were four zones in the joint:NZ, TMAZ, HAZ and BM. There was a large difference of grain size, grain shape and grain boundary. Cube and S textures in BM transformed into shear texture during FSW. HABs distribution were most significant in NZ followed by RS and then by AS. A large number of dislocations and precipitates were observed in NZ and TMAZ.